Geodetic Data for USGS Glaciers: Orthophotos, Digital Elevation Models, Glacier Boundaries and Surveyed Positions ... - Christopher J. Mcneil; Caitlyn E Florentine; Valerie A Bright; Mark J. Fahey; Evan McCann; Christopher F. Larsen; Evan E Thoms; David E. Shean; Lisa A Mckeon; Rod S. March; William Keller; Erin N Whorton; et al. (U.S. Geological Survey, 2019)
This data release provides geodetic measurements collected since the mid-1940s to characterize the surface elevation, area, and motion of glaciers studied by the U.S, Geological Survey. The primary glaciers of focus are the Benchmark Glaciers of North America which include Gulkana, Wolverine, and Lemon Creek Glaciers in Alaska, Sperry Glacier in Montana, and South Cascade Glacier in Washington state (USA). The data include: historic and contemporary glacier boundary outlines, point data from GNSS surveys, Digital Elevation Models (DEM), and orthorectified aerial photos and satellite imagery (Orthos). This data release is updated periodically. The "versionHistory.txt" file included with this data release describes updates made in each version. ...